Settlement and recruitment of the crab Halicarcinus planatus (Crustacea: Decapoda: Hymenosomatidae) in Golfo San Jorge, Argentina - Vinuesa, Julio Hector; Varisco, Martin Alejandro; Escriche, Florencia (Journal of the Marine Biological Association of the United Kingdom)
The settlement and recruitment of the small brachyuran crab Halicarcinus planatus from the central area of Golfo San Jorge, south-western Atlantic Ocean, was studied. Three different artificial collectors were evaluated: smooth-surface panels, panels covered with synthetic lawn and ballasted plastic boxes filled with remains of fishing nets. In addition, plankton samples were taken monthly and water salinity and temperature were recorded. Between July 2006 and June 2007, the collectors were deployed monthly in the subtidal zone of two nearby localities and collected two months later. The recovered crabs were classified into four stages: settlers, recruits, advanced juveniles and mature crabs. There were differences in the presence of stages among collector types and seasons but not between localities. Settlers and recruits were abundant on the panels with synthetic lawn, while late juvenile and mature females were more frequent in the boxes. Larval stages occur between July and February, and only zoeas I and II were found. The males, which were only represented by early juveniles, were exclusively found on the panels with synthetic lawn, from where they would subsequently migrate to cryptic habitats such as the holdfast of Macrocystis pyrifera. Settlement occurs between September and April. Settlers showed a peak in abundance during November-December, while the recruits showed two peaks, one in December and the other in February-March. For late juveniles, the maximum abundance was recorded in April-May. Ovigerous females were found between May and September, when the experiment ended. Settlement and recruitment of H. planatus in Golfo San Jorge occur over a prolonged period. Individuals may undergo shifts in microhabitat use during this period, probably related to the search for food and shelter, and avoidance of predation and cannibalism. Fil: Vinuesa, Julio Hector. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: ...